A 3D numerical study to evaluate optimum collector inclination angle of Manzanares solar updraft tower power plant. (15th September 2021) - Keshari, Sajjan Raj; V.P., Chandramohan; Das, Pritam
Highlights: 15 models were developed with different collector angle ( θ ) to analyse the impact. Velocity, pressure, power, collector and overall efficiencies were estimated. Enhancement of air velocity and theoretical power were noticed at θ  = 6°. θ more than 6° created extensive recirculation and vortices inside the canopy. A correct turbine location was proposed for Manzanares plant. Abstract: In this paper, a three-dimensional turbulent study was carried out on Manzanares (Spain) plant to study the effects of collector inclination angle ( θ ). Different ranges of θ (30–0°) with more than 15 models were considered for the analysis. An optimized θ has been proposed based on the estimated parameters such as air velocity, pressure drop, absorber and air temperatures, power developed, collector efficiency, and overall efficiency ( ηcoll and ηo ). At θ  = 6°, an increment of 9.16% in theoretical power ( Pth ) and a 10.68% increase in air velocity were observed at the chimney base (CB) compared to the horizontal collector plant. Any further increase in θ (greater than 7°) resulted in recirculation of air particles within the collector canopy, leading to obstruction of flow. Any value of θ lesser than 6° resulted in a drop in the major outputs such as Pth, ηcoll, and ηo . Eventually, θ  = 6° has been proposed as optimized inclination. The dynamic pressure difference was maximum at a chimney height of 2.5 m from CB; therefore, this was the preferred location for turbine fitment. The results were compared with the experimental data of the Manzanares plant, and a very favorable agreement was noticed.